COVID-19’s effects on children in North Macedonia: Rapid analysis and policy proposals - Petreski, M.; Petreski, B.; Tomovska-Misoska, A.; Gerovska Mitev, M.; Parnardzieva-Zmejkova, M.; Dimkovski, V.; Morgan, N. (UNICEF, 2020)
The pandemic caused by the Covid-19 is harming social, educational and health wellbeing of children, with the most vulnerable being hit the hardest. The study shows that Covid-19 has exacerbated child poverty in North Macedonia. It has likely put additional 16,000 children below the poverty threshold increasing the relative child poverty rate from 29.3 per cent to the estimated 33.3 per cent. In addition, children from single-parent households receiving guaranteed minimum assistance faced increased risk of food poverty amid suspension of free meals due to the closure of preschool and school facilities. Family violence increased during Covid-19, with children being nearly 10 percent of the victims.